Development of an inhibitor in a child with severe hemophilia B: treatment with immunosuppression and an extended desensitization protocol. Issue 6 (September 2019) - Roberts, Jonathan C.; Jesudas, Rohith; Tarantino, Michael D.
Abstract : N/A: Development of neutralizing alloantibodies in hemophilia B is a less common, but clinically challenging phenomenon. Novel therapeutics for hemophilia B have recently been developed and reports of clinical experience with these agents outside of clinical trials are needed. We report development of an inhibitor in a child with severe hemophilia B, and subsequent immune tolerance induction using an extended desensitization protocol with the addition of immunosuppression. This case highlights successful management of a rare complication in a rare bleeding disorder and the need for additional investigation into this infrequent and clinically challenging occurrence.